2021
DOI: 10.1021/acs.orglett.1c02442
|View full text |Cite
|
Sign up to set email alerts
|

Nickel-Catalyzed One-Pot Carbonylative Synthesis of 2-Mono- and 2,3-Disubstituted Thiochromenones from 2-Bromobenzenesulfonyl Chlorides and Alkynes

Abstract: A nickel-catalyzed one-pot carbonylation reaction of 2-bromobenzenesulfonyl chlorides with alkynes for the synthesis of thiochromenones has been established. Both terminal and internal alkynes were suitable substrates in this carbonylative transformation, and a broad range of 2-mono- and 2,3-disubstituted thiochromenone products were obtained in moderate to good yields with quite high functional group compatibility. Notably, this procedure presents the first example of nickel-catalyzed carbonylative synthesis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 55 publications
0
9
0
Order By: Relevance
“…[ 10 ] Very recently, Wu, Qi and coworkers developed another nickel‐catalyzed carbonylative strategy using 2‐bromo‐arylsulfonyl chloride as the starting material. [ 11a ] They also reported a rhodium‐catalyzed carbonylative strategy using aryl disulfide as starting material, [ 11b ] which only led to benzothiochromenones products. Inspired by these reactions and our previous metal‐catalyzed C—H functionalization [ 12 ] and carbonylation approach from anilines to six‐membered quinolinones, [ 12a ] and the carbonylative coupling reactions, [ 13 ] we envisioned that a CO insertion strategy could be designed and applied in the poly‐substituted thiochromenones synthesis.…”
Section: Background and Originality Contentmentioning
confidence: 99%
“…[ 10 ] Very recently, Wu, Qi and coworkers developed another nickel‐catalyzed carbonylative strategy using 2‐bromo‐arylsulfonyl chloride as the starting material. [ 11a ] They also reported a rhodium‐catalyzed carbonylative strategy using aryl disulfide as starting material, [ 11b ] which only led to benzothiochromenones products. Inspired by these reactions and our previous metal‐catalyzed C—H functionalization [ 12 ] and carbonylation approach from anilines to six‐membered quinolinones, [ 12a ] and the carbonylative coupling reactions, [ 13 ] we envisioned that a CO insertion strategy could be designed and applied in the poly‐substituted thiochromenones synthesis.…”
Section: Background and Originality Contentmentioning
confidence: 99%
“…The desired thiochromenones were produced via a reductive elimination step. Very recently, the same group also reported a nickel-catalyzed carbonylative cyclization of 2-bromosulfonyl chlorides and alkynes toward the synthesis of thiochromones in a one-pot manner . The reaction begins with the PPh 3 reduction of 2-bromosulfonyl chloride to give disulfide, which was converted to 2-bromothiophenol in the presence of Mo­(CO) 6 and H 2 O.…”
Section: Intermolecular Carbonylative Multifunctionalization Of Alkynesmentioning
confidence: 99%
“…Very recently, the same group also reported a nickel-catalyzed carbonylative cyclization of 2-bromosulfonyl chlorides and alkynes toward the synthesis of thiochromones in a one-pot manner. 86 The reaction begins with the PPh 3 reduction of 2-bromosulfonyl chloride to give disulfide, which was converted to 2-bromothiophenol in the presence of Mo(CO) 6 87 In 1997, Matsuda et al reported rhodium-catalyzed cyclocarbonylation of substituted propargyl alcohols toward the synthesis of (Z)-α-(triorganosilyl)methylene-β-lactones (Scheme 34). 88 Both steric and electronic factors play a vital role in the formation of β-lactones, and the reaction yield was dramatically increased when using bulkier silane t BuMe 2 SiH and stronger base DBU.…”
Section: Intermolecular Carbonylative Multifunctionalization Of Alkynesmentioning
confidence: 99%
“…[11] Regarding the many possibilities to construct thiochromenones, the annulation of ortho-thioaryl ynones is an elegant approach. [12] In this context, the use of sulfur-based reaction partners to construct 3-sulfenyl-decorated thiochromenone derivatives was scarcely explored, and general protocols are still required. [13] For example, in 2019, Song and co-workers [13a] described a broad study using this strategy, employing several radical species, including phosphorus-, sulfur-, Csp 3 -, and Csp 2centered ones.…”
Section: Introductionmentioning
confidence: 99%